Impact of Hypothyroidism on Echocardiographic Characteristics of Patients With Heart Valve Disease: A Single-Center Propensity Score-Based Study - Zhai, Tianyu; Cai, Zhenqin; Zheng, Jiayu; Ling, Yan (Frontiers in Endocrinology, 2020)
Background: Hypothyroidism is known to be correlated with multiple heart diseases. However, the influence of hypothyroidism on the patients with heart valve disease (HVD) is still unclear. The purpose of our study was to investigate the impact of hypothyroidism on echocardiographic characteristics of patients with heart valve disease. Methods: We conducted a retrospective cohort study which included 2128 patients with HVD, and they were divided into euthyroid, subclinical hypothyroidism (SCHypoT), and overt hypothyroidism (OHypoT) group. Echocardiographic characteristics before and after valve surgery between groups were compared by using propensity score (PS) analysis. Kaplan-Meier analysis was used to compare the percent of recovery of left atrial (LA) enlargement between groups. Results: Overall, 463 patients had hypothyroidism (404 SCHypoT patients and 59 OHypoT patients), and 1665 patients were euthyroid. At baseline, hypothyroidism was associated with significantly higher left atrial diameter (LAD), interventricular septum thickness, left ventricular posterior wall thickness, pulmonary artery systolic pressure, and lower left ventricular ejection fraction. After valve surgery, only LAD remained significantly higher in the patients with hypothyroidism. Additionally, patients with hypothyroidism had a significantly lower recovery rate of LA enlargement after valve surgery compared with euthyroid patients. Conclusion: Hypothyroidism was associated with a larger LAD in patients with HVD before and after surgery, which may suggest that hypothyroidism is a risk factor of LA enlargement of HVD. Besides, hypothyroidism was associated with a significantly lower recovery rate of LA enlargement after valve surgery.